ЖИВАЯ АРХИТЕКТУРА: УСТОЙЧИВЫЙ ПОДХОД К ПРОЕКТИРОВАНИЮ ЖЕНСКИХ ЦЕНТРОВ ВОССТАНОВЛЕНИИ. (KIUT Publication, 2025)
This article is dedicated to exploring the application of biophilic architecture principles in the design of women's rehabilitation centers. The aim is to create spaces that not only fulfill functional needs but also contribute to the emotional and psychological recovery of women who have experienced trauma. In the context of modern social and ecological challenges, traditional design methods often fail to provide the necessary conditions for deep healing. The paper discusses biophilic architecture principles, such as bioarchitecture, biophilic design, the use of ecological technologies, and sustainability. The role of natural elements and sensory comfort in the healing process is analyzed. The importance of security, privacy, and adaptable spaces for women is explored. Conceptual approaches, including territorial placement, zoning, creation of therapeutic gardens, and the use of natural materials, are discussed. The conclusion emphasizes the significance of integrating interdisciplinary knowledge from psychology, ecology, and sociology into architectural practice, which can help create supportive and living spaces for healing.